A RENÚNCIA SEXUAL PELO REINO: A IMPORTÂNCIA DA RENÚNCIA SEXUAL PARA A LIDERANÇA DA MULHER EM ATOS DE PAULO E TECLA - Araujo, Kellen Christiane Rodrigues de (2015)
The purpose of this research is to analyze the work the Acts of Paul and Thecla, focusing on the importance of sexual abstinence for womens leadership. A topic that was essential for women to conquer their space and power in society and this way get to make their voice heard, even though not as considerable. By examining the Apocryphal Acts of Paul and Thecla, its main characteristics and composition can be observed, also with its origin and interpretation by communities and leaders in the beginning of Christianity. Sought to portray this research, justifying the Greek romance, presenting their similarities with the Acts of Paul and Thecla and thus highlight the influence of Greek writing on the apocryphal text in its way of structuring. It was presented the definitions of sexual abstinence, leadership and martyrdom always stressing themes with the figure of the woman, addressing the issue of the body and society and demonstrating how these themes inspired speeches in early Christianity. Referring to the writings of Acts Apocrypha, we present the origin of communities of celibate women who influenced the writing of texts, reporting why the Acts were written and how they were disseminated in other communities. About martyrdom it was described its origins and how Christians saw in this action an approach to God and how martyrdom prepared Theclas life to become an agent of Gods word.